A comparison of molar root canal preparation using stainless-steel and nickel-titanium instruments - Porto Carvalho, Luciana Arantes; Bonetti, Idomeo [UNESP]; Gagliardi Borges, Marco Aurelio [UNESP] (Elsevier, 1999)
Fifty-four extracted human mandibular molars were embedded and sectioned at two levels. The reassembled mesial root canals were prepared with stainless-steel hand K-files (Flexofiles) and either Nitiflex or Mity nickel-titanium hand K-files using a push-pull anticurvature filing technique. Each of the three experimental groups contained 36 mesial canals randomly distributed. Superimposed pre- and postinstrumentation cross-sectional root images were magnified using a stereomicroscope and transferred to a computer for measurement and statistical analysis. The direction and extent of canal center movement were evaluated. At the apical level, the groups produced no significant difference of direction of canal center movement. In cervical sections, all groups tended to move in a distolingual direction. The three groups, however, produced no significant difference in the cervical sections in the extent of canal center movement. In apical sections, Nitiflex produced the least canal center movement. Copyright © 1999 by The American Association of Endodontists.
Keywords: nickel; stainless steel; titanium; titanium nickelide; analysis of variance; chi square distribution; comparative study; dental equipment; endodontics; human; image processing; instrumentation; mandible; molar tooth; nonparametric test; randomization; Analysis of Variance; Chi-Square Distribution; Dental Instruments; Humans; Image Processing, Computer-Assisted; Mandible; Molar; Nickel; Random Allocation; Root Canal Preparation; Stainless Steel; Statistics, Nonparametric; Titanium